Intelligent Decision Technologies 2016 : Proceedings of the 8th KES International Conference on Intelligent Decision Technologies (KES-IDT 2016) – Part I /: Proceedings of the 8th KES International Conference on Intelligent Decision Technologies (KES-IDT 2016) – Part I. (2016) - Unknown
No abstract available